Pelaksanaan Pembelajaran Ibadah Wudhu di Taman Kanak-Kanak Islam Terpadu Dar El-Iman 2 Kota Padang - Revita, Desi; Hartati, Sri (Jurnal Ilmiah Pesona PAUD, 2020)
This study aims to describe the implementation of learning ablution using a qualitative approach, descriptive method. Reseacrh informants are teachers. Data collection techniques are observation, interviews, and documentation. Data analysis techniques with data triangulation techniques. The results of the implementation of learning ablution in the Integrated Islamic Kindergarten Dar El-Iman 2 Padang City were carried out well. The activities of implementing ablution leraning are carried out using simulation methods and exercises. The simulation method shows the teacher who directly teaches the implementation of ablution to children, the steps from beginning to end using hand mevements then the child follows. The teacher signals to the child as if in front of him there is water when in fact it is not, this is done to make it easier for the child to remember the steps of performing ablution. In the practice method of performing ablution worship every week, so that children can understand and apply it in everyday life and children can do the implementation of ritual ablution as taught by the Prophet Muhammad. The implementation of ablution learning has been effective.Â Keyword : Implementation of worship learning, worship ablution.